The molecular mechanism underlying dermatomyositis related interstitial lung disease: evidence from bioinformatic analysis and in vivo validation - Zeng, Li; Tang, Yiping; Zhang, Yichen; Yue, Li; Ma, Gang; Ye, Xumin; Yang, Lijing; Chen, Kai; Zhou, Qiao (Frontiers in Immunology, 2023)
Background: Dermatomyositis (DM) is an autoimmune and inflammatory disease that can affect the lungs, causing interstitial lung diseases (ILD). However, the exact pathophysiological mechanisms underlying DM-ILD are unknown. Idiopathic pulmonary fibrosis (IPF) belongs to the broader spectrum of ILD and evidence shows that common pathologic pathways might lie between IPF and DM-ILD.We retrieved gene expression profiles of DM and IPF from the Gene Expression Omnibus (GEO) and utilized weighted gene co-expression network analysis (WGCNA) to reveal their co-expression modules. We then performed a differentially 删除了: is 40 删除了: s 41 删除了: Gene expression profiles of DM and IPF were 42 retrieved from the Gene Expression Omnibus (GEO). Their 43 co-expression modules were revealed by utilizing weighted 44 gene co-expression network analysis (WGCNA).